Flow Diverter Stenting for Symptomatic Intracranial Internal Carotid Artery Aneurysms: Clinical Outcomes and Factors for Symptom Improvement - Keisuke NISHIMOTO; Tomohiko OZAKI; Tomoki KIDANI; Shin NAKAJIMA; Yonehiro KANEMURA; Hiroki YAMAZAKI; Toshiyuki FUJINAKA (Neurologia Medico-Chirurgica, 2023)
Flow diverter (FD) stenting is expected to improve cranial nerve symptoms caused by aneurysms via the theoretical reduction of the mass effect by promoting spontaneous thrombosis through the flow diversion effect. However, the factors involved in symptom improvement after treatment remain unclear. This study was performed to identify factors for symptom improvement after FD stenting and the symptom improvement rate of each impaired cranial nerve. We retrospectively evaluated 33 patients who underwent FD stenting for symptomatic internal carotid artery aneurysms at our institution from January 2016 to June 2021. Twenty-three (69.7%) patients had resolved or improved symptoms after 1 year of treatment. The optic nerve was affected in 12 patients; the oculomotor nerve, in 16; the trigeminal nerve, in 2; and the abducens nerve, in 13. There was no statistically significant difference in the symptom improvement rate of each impaired cranial nerve. The patients were classified into the improved and nonimproved groups based on their symptoms after 1 year of treatment, and the factors related to the symptoms were analyzed. The time from onset to treatment was significantly shorter in the improved group than in the nonimproved group (197.1 and 800 days, respectively; p = 0.023). There were no significant differences in age, aneurysm diameter, adjunctive coil embolization, partial thrombosis, change in mass diameter on magnetic resonance imaging, or aneurysm occlusion rate on angiography between the two groups. These results suggest that early treatment after the onset of aneurysm-induced cranial neuropathies increases the likelihood of symptom improvement.